Injectable hydrogels as a delivery system for bone regeneration - Pereira, Isabel (2017)
The worldwide incidence of bone disorders is increasing, mainly due to an ageing population. The lack of effective treatments is pushing the development of synthetic bone substitutes (SBSs). This chapter provides an overview of the currently available ceramic SBSs and describes the main advantages and limitations of commercially available ceramic-based injectable bone substitutes (IBSs), such as, bone cements and polymerceramic compositespastes and putties. The combination of injectable hydrogels and ceramic granules is emerging as a well-established trend. Particularly, in situ gelation hydrogels arise as a new IBSs generation. Herein, we present the recent progress in the development and application of hydrogel-based IBSs. Finally, the medical devices regulatory process is thoroughly discussed. Additionally, in view of the translation of IBSs into clinical practice, the main differences of the regulatory process in Europe and United States are highlighted.